Post-burn popliteal fossa flexion contracture: our experience about a case in N’Djamena (Chad) - Adendjingue, Daniel Mossalbaye; Andjeffa, Valentin; Moussede, Madengar; Ouangre, Abdouramane; Dingamnodje, Magloire; Nodjiath, Emery N. (European Scientific Journal, ESJ, 2025)
Introduction: The functional sequels of burns, including knee contracture, are common in children in southern countries due to very limited access to specialized care structures. The treatment is surgical, accompanied by physiotherapy to improve the functional result. Case report: We report the case of an 11-year-old female patient, admitted to the surgery department after three. She suffered from sequelae of thermal flame burn of the trunk and lower limbs. She was treated in a rural hospital, and the evolution was complicated by a contracture of the left popliteal fossa and incomplete healing of the wound. The treatment of the wound was done for thirty days, allowing for an optimal local condition. This was until the suppuration completely stopped (after thirty days). Complete healing was not achieved but the wound was clean, and the C-Reactive Protein was normal. Surgery to release the flange was possible after two months. A plasty to release the flange was carried out eight weeks later by a “chevron” lengthening tenotomy of the hamstring muscles and transversal fascial incisions (to discharge the gastrocnemius muscles). Conclusion: A posterior femoropedious cast splint in extension was placed. Physiotherapy was started early, and a skin graft (thin and total) was performed eight weeks post-operatively. The evaluation at 18 months was good, with a slight limp when walking.